2013
DOI: 10.1111/vco.12035
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genomic mutation and immunohistochemistry of platelet‐derived growth factor receptors in canine vascular tumours

Abstract: We examined whether mutation of the platelet-derived growth factor receptor protein tyrosine kinase (PDGFR)-α and PDGFR-β genes contributes to their overexpression in canine vascular tumours. Genomic sequences of trans- or juxtamembrane regions of PDGFR-α and PDGFR-β were analysed with immunohistochemical staining and polymerase chain reaction-direct sequencing using DNA from paraffin-embedded neoplastic tissues of 27 hemangiosarcomas (HSAs) and 20 hemangiomas (HAs). Immunohistochemically, 75% of the HA cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…Even if an autocrine receptor activation may occur in T-cell lymphomas, it is still not known if this is a critical or a contributing event in its development. Also, structural aberrations of PDGFRs that lead to overexpression or expression of abnormal proteins have been described in canine vascular tumours (Abou Asa et al, 2013), and will be taken into consideration in the next studies. PDGF-B and PDGFRs may represent new therapeutic target in canine T-cell lymphomas and future studies will be directed to collect clinical data to further understand a potential prognostic role of these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Even if an autocrine receptor activation may occur in T-cell lymphomas, it is still not known if this is a critical or a contributing event in its development. Also, structural aberrations of PDGFRs that lead to overexpression or expression of abnormal proteins have been described in canine vascular tumours (Abou Asa et al, 2013), and will be taken into consideration in the next studies. PDGF-B and PDGFRs may represent new therapeutic target in canine T-cell lymphomas and future studies will be directed to collect clinical data to further understand a potential prognostic role of these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, a recent whole-exome sequencing study of a small cohort of 20 angiosarcomas showed that the top recurrently mutated genes were PIK3CA and TP53 (29) . Earlier candidate gene studies of canine angiosarcomas have reported mutations in TP53 (30) , PTEN (31) , and PDGFRA and PDGFRB (32) . An analysis of somatic copy number aberrations in visceral angiosarcomas from five breeds found that VEGFA showed frequent copy number gain, while CDKN2A was frequently deleted (33) .…”
Section: Introductionmentioning
confidence: 98%
“…This is again reflected in the relatively lower median expression score of 54.6 compared with VEGFR expression. The predominant PDGFR expression pattern in the current study was cytoplasmic (PDGFR‐α, 87.9%; PDGFR‐β, 63.5%) as already reported in previous studies with canine vascular tumours . Interestingly, this study also demonstrated a strong stromal expression for both PDGFRs (PDGFR‐α in 15.5%; PDGFR‐β in 60.9%) as compared with VEGFR (8.5%).…”
Section: Discussionmentioning
confidence: 55%